2015
DOI: 10.1097/md.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Venous Thromboembolism After Spine Surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 19 publications
2
70
1
Order By: Relevance
“…In adult total hip and knee arthroplasty, the rate of predischarge symptomatic VTE approaches 2% even after thromboprophylaxis, although many more VTEs occur postdischarge and are asymptomatic. 17 In adult spine surgery, symptomatic VTE occurs in 1.5% of patients; 18 this rate is □10 times the rate in our observed pediatric spine population (0.10%). Therefore, the low rate of occurrence in pediatric orthopaedic surgery patients, compared with adults, calls into question whether routine thromboprophylaxis should be indicated.…”
Section: Discussionmentioning
confidence: 67%
“…In adult total hip and knee arthroplasty, the rate of predischarge symptomatic VTE approaches 2% even after thromboprophylaxis, although many more VTEs occur postdischarge and are asymptomatic. 17 In adult spine surgery, symptomatic VTE occurs in 1.5% of patients; 18 this rate is □10 times the rate in our observed pediatric spine population (0.10%). Therefore, the low rate of occurrence in pediatric orthopaedic surgery patients, compared with adults, calls into question whether routine thromboprophylaxis should be indicated.…”
Section: Discussionmentioning
confidence: 67%
“…Four studies [31,33–35] reported relation between history of smoking and incidence of VTE. The result showed that a history of smoking did not affect incidence of VTE ( P  = 0.13, OR = 1.20, 95% CI [0.95, 1.51]; heterogeneity: P  = 0.36, I 2  = 6%, fixed-effects model; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [28,31,32] reported relation between walking disability preoperation and incidence of VTE. The result showed that walking disability preoperation significantly increased the incidence of VTE ( P  < 0.00001, OR = 4.80, 95% CI [2.53, 9.12]; heterogeneity: P  = 0.64, I 2  = 0%, fixed-effects model; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the preoperative phase, certain high-risk modifiable risk factors, mainly insulin-dependent diabetes, smoking, and long-term steroid use, should be identified and mitigated. 80,83,125,127,141,143,159 In the intraoperative phase, attention to physiological parameters, use of neuromonitoring adjuncts, judicious use of autologous blood transfusions, and shorter surgical times all reduce the likelihood of complications. 60,155 In the postoperative phase, appropriate mechanical and chemical prophylaxis for venous thrombosis, timely removal of urinary catheters, meticulous blood glucose control, appropriate mobilization of patients, and close neurological monitoring can reduce the incidence of these events.…”
Section: Rationalementioning
confidence: 99%
“…43,87,100 Physical therapy, including gait training, has also been shown to improve mobility and reduce the incidence of complications such as DVT and PE. 143 The time frame during which these rehabilitation programs have shown to have proven efficacy span the period from immediately postoperatively with inpatient rehabilitation services to programs starting 4 to 6 weeks postsurgery. Accurate assessment of postsurgical physical therapy assignment is essential to assess the impact of these interventions, better understand overall resource utilization in spine care, and assist in the planning of continuing care.…”
Section: Rationalementioning
confidence: 99%